Advances in In Situ SiC Growth Analysis Using Cone Beam Computed Tomography - Salamon, Michael; Arzig, Matthias; Uhlmann, Norman; Wellmann, Peter (Materials Science Forum, 2019)
Computed Tomography is becoming a valuable method for the in-situ monitoring of vapor grown silicon carbide single crystals [1]. Already the two-dimensional X-ray radiography has shown the potential of surveilling the growth process [2] and its characteristic features like the evolution of the facet, the crystal volume or the source material structure from one imaging plane. Even though the demands on imaging capability of the applied X-ray components used for a tomographic analysis are higher than for two-dimensional imaging, the extension of this method to the third dimension is highly beneficial. It allows investigating the full geometry and three-dimensional location of the features and by this provides a more accurate analysis. In this contribution we present the physical characteristics and the latest advances of our technique for the visualization of facets.
Keywords: 3D In Situ Analysis; Computed Tomography; PVT Growth Process Surveillance